2006
DOI: 10.1097/01.sla.0000197706.21803.a1
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Recurrence After Liver Resection for Hepatocellular Carcinoma

Abstract: Early and late recurrences are linked to different predictive factors. The modality of presentation of the recurrence together with the feasibility of a radical treatment are the best determinants for the prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

41
649
8
16

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 752 publications
(730 citation statements)
references
References 18 publications
41
649
8
16
Order By: Relevance
“…In our study, we found that the degree of liver cirrhosis is the only significant risk factor for postoperative late intrahepatic recurrence. This finding was consistent with previous reports (Poon et al, 2000;Portolani et al, 2006). Poon et al (2000) investigated 246 HCC patients underwent curative resection and identified cirrhosis as the only significant risk factor for late recurrence.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, we found that the degree of liver cirrhosis is the only significant risk factor for postoperative late intrahepatic recurrence. This finding was consistent with previous reports (Poon et al, 2000;Portolani et al, 2006). Poon et al (2000) investigated 246 HCC patients underwent curative resection and identified cirrhosis as the only significant risk factor for late recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…Liver cirrhosis is established through repetitive necroinflammation and regeneration. Several investigators have also reported that liver cirrhosis is significant risk factor for recurrence after resection for HCC (Portolani et al, 2006;Sumie et al, 2008;Ho et al, 2012). In our study, we found that the degree of liver cirrhosis is the only significant risk factor for postoperative late intrahepatic recurrence.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In contrast, our univariate analysis showed increased levels of cfDNA in HCC patients with early IHR. Most early IHRs can be attributed to intrahepatic metastasis of cancer cells and are detected in 30 -50% of patients within 1 or 2 years after surgery, limiting the potential for surgical cure of HCC (Tung-Ping Poon et al, 2000;Iizuka et al, 2003;Llovet et al, 2003;Matoba et al, 2005;Portolani et al, 2006). Thus, the increased levels of serum cfDNA are related to the high metastatic potential, but not to the appearance of de novo tumour, of this type HCC.…”
Section: Discussionmentioning
confidence: 99%